Selenium Protects Yellow Catfish (Tachysurus fulvidraco) from Low-Temperature Damage via the Perspective Analysis of Metabolomics and Intestinal Microbes - Junru Hu; Lei Wang; Guoxia Wang; Hongxia Zhao; Huijie Lu; Kai Peng; Wen Huang; Zhenxing Liu; Ding Liu; Yuping Sun (Fishes, 2024)
The effects of selenium supplementation in Tachysurus fulvidraco (T. fulvidraco) on low-temperature stress are not known. In this study, 280 healthy T. fulvidraco were divided into two groups, the G0 group (a control group) and the T0 group (a selenium treatment group on a 0.22 mg/kg diet), for a 6-week feeding time. Then, low-temperature stress (water temperature dropped from 26 to 13 °C, with a rate of 1 °C/h) was administered after that. The feeding results showed that selenium increased the percent weight gain (PWG), specific growth rate (SGR), and survival rate (SR) of T. fulvidraco and decreased the feed conversion rate (FCR), but these differences were not significant (p > 0.05). Under low temperatures, selenium still has no significant effects on antioxidant indexes such as glutathione peroxidase (GSH-Px) activity, superoxide dismutase (SOD) activity, and malondialdehyde (MDA) content in serum (p > 0.05). However, metabolomic analysis revealed that selenium caused changes in lipids and lipid-like molles, organic acids and their derivatives, and fatty acyls. Choline, linoleic acid, and glycerophospholipid metabolism pathways; d-arginine and d-ornithine metabolism; valine, leucine, and isoleucine degradation; and biosynthesis pathways, as well as pyrimidine metabolism pathways, were activated to produce these metabolites to combat against this stress. In addition, selenium increased the diversity of intestinal microbes in T. fulvidraco and decreased the relative abundance of Plesiomonas. However, the combined analysis showed the intestinal microbe changes did not affect metabolite production. In summary, selenium activated lipid, carbohydrate, and amino acid metabolism for energy substance provision, reduced the oxidation and production of other harmful substances, and increased the intestinal microbe diversity of T. fulvidraco to improve resistance to low-temperature stress.